A Curious Lobe - Andréa Chabot-Naud; George Rakovich; Karine Chagnon; Denise Ouellette; Gilles Beauchamp (Canadian Respiratory Journal)
A case of azygos lobe is presented. An azygos lobe is an accessory lobe of the lung that may occasionally be confused with a pathological process such as a bulla, lung abscess or neoplasm. Its pathogenesis is discussed, as are the characteristic x-ray features that enable an accurate diagnosis.